2006
DOI: 10.1111/j.1365-3083.2006.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Spray Immunization May Be an Alternative to Intranasal Vaccine Delivery to Induce Systemic Antibodies but not Nasal Mucosal or Cellular Immunity

Abstract: Sixty-five healthy adult volunteers were immunized four times at 1-week intervals with an inactivated whole-virus influenza vaccine based on the strain A/New Caledonia/20/99 (H1N1) without adjuvant. The vaccine was administered as nasal spray with a newly developed device to secure intranasal delivery (OptiMist TM , OptiNose AS, Oslo, Norway), as regular nasal spray, nasal drops or as an oral spray. Significant IgA-antibody responses in nasal secretions were induced in volunteers immunized intranasally but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…This is often used in animal studies where the animals are anesthetized or sedated, but can also be done in humans even without local anesthetics if care is taken to minimize contact with the sensitive mucosal membranes [50]. This method is, however, not suitable for self-administration.…”
Section: Nasal Drug Delivery Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is often used in animal studies where the animals are anesthetized or sedated, but can also be done in humans even without local anesthetics if care is taken to minimize contact with the sensitive mucosal membranes [50]. This method is, however, not suitable for self-administration.…”
Section: Nasal Drug Delivery Devicesmentioning
confidence: 99%
“…In contrast to the self-administration with the OptiNose device, the nasal drops were delivered by an assistant inserting the pipette tip in a controlled manner beyond the nasal valve with the neck extended. These results suggest that Bi-Directional™ devices are a practical delivery method capable of producing a clinically relevant broader and deeper distribution of vaccines to the nasal respiratory mucosa, areas rich in dendritic cells and aggregates of lymphoid tissue, offering potential for a range of vaccines to produce improved immune response in non-parenteral delivery forms [24, 50]. …”
Section: Nasal Drug Delivery Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel nasal spray device (Optinose BD device) has been recently developed and is claimed to address most of the challenges of nasal vaccine delivery 231, 234, 235. This bidirectional nasal delivery device is a newer concept that takes advantage of the posterior connection between the nasal passages which persists when the soft palate automatically closes during oral exhalation.…”
Section: Delivery Devices For Intranasal Vaccine Administrationmentioning
confidence: 99%
“…Furthermore, nasal delivery devices like, Lyphodose ® and OptiNose ® have been developed to deliver the exact amounts of powders in the nasal cavity. 22,23 Dermal administration of dried influenza vaccines have been tested in clinical and preclinical studies via two methods, jet injectors and micro-needles respectively. Clinical Phase1 studies have shown the successful use of the powderject been used for stabilization i.e., trehalose and inulin.…”
Section: Wwwlandesbiosciencecom Human Vaccines 855mentioning
confidence: 99%